Somalia's struggle to integrate traditional and modern governance: The 4.5 formula and 2012 provisional constitution - Ahmed, Nasteha (AUC Knowledge Fountain, 2019)
The objective of this project is to assess the impact of Somalia’s 4.5 power sharing formula on the consolidation of post-conflict governance. Per the peace agreement, seats in parliament are awarded to the four major clans which also dominate the election process. This has led to the perpetuation of many of the same social dynamics that lead to conflict in the past. Even though the 4.5 formula was not included in the constitution adopted in 2012, the elections methods from the formula were utilized in 2017 presidential elections. Although the goal is to move towards a one-man-one vote system, the use of the 4.5 formula in the 2017 elections points to a struggle in establishing this process. This project will argue that clan influence is likely to remain a challenge for Somalia’s transition to democracy until a civilian based voting system is put into place. This research employed the works Ball (1996) and Papagianni (2007) to analyze the success as well as the failures of rebuilding Somalia and impact of the 4.5 formula had on this process.